"Doing commensality", eating together in the visiting room: families, food, and commensality - Adams, Maria (The role of food in resettlement and rehabilitation, 2026)
There is substantial literature on the importance of food in family life, but much less on women who are incarcerated and who therefore have limited opportunities to eat with their families. The space of the visiting room offers one opportunity, albeit restricted in time and space, to do this, as well as making the visit more enjoyable for family members who have often travelled long distances to see their loved one (Comfort, 2008; Jardine, 2019; Adams, 2022). In this chapter, we will examine how we can integrate the concepts of eating with the family and prison to contribute to the dialogue on passing the time. We will develop the notion of “Doing Commensality” to understand the relationship between how women in prison and their families experience meaningful eating practices in the prison visiting room and beyond. Furthermore, we will explore whether these types of eating practices can be a means to reunite and to strengthen familial bonds. The aims of this chapter will include: (1) to explore the importance of food practices that are adopted in the confinement of the prison visiting room and the home; (2) to identify good practice and challenges of eating together in the prison visiting room of women incarcerated and their families; and lastly to see how the pandemic affected food practices in the prison visiting room. This knowledge and understanding of the importance of having the opportunity to eat together in the visiting room will contribute to policy and practical recommendations to improve the quality and provision of food in a family-friendly environment, to benefit those incarcerated and those visiting.